2005
DOI: 10.1007/s11373-005-9036-8
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives in intronic micro RNAs (miRNAs)

Abstract: SummaryMicroRNAs (miRNAs), small single-stranded regulatory RNAs capable of interfering with intracellular messenger RNAs (mRNAs) that contain either complete or partial complementarity, are useful for the design of new therapies against cancer polymorphism and viral mutation. Numerous miRNAs have been reported to induce RNA interference (RNAi), a post-transcriptional gene silencing mechanism. Intronic miRNAs, derived from introns by RNA splicing and Dicer processing, can interfere with intracellular mRNAs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…Expression levels of intronic miRNAs and their host genes often are highly correlated, presumably because they are co-transcribed [16,18]. In the case of miR-103, the miRNA expression level were indirectly correlated with expression coefficients of 0.638 (PANK2) and 0.270 (PANK3) [16].…”
Section: Bioinformatics Predict a Role For Mir-103/mir-107 Paralogs Imentioning
confidence: 99%
See 2 more Smart Citations
“…Expression levels of intronic miRNAs and their host genes often are highly correlated, presumably because they are co-transcribed [16,18]. In the case of miR-103, the miRNA expression level were indirectly correlated with expression coefficients of 0.638 (PANK2) and 0.270 (PANK3) [16].…”
Section: Bioinformatics Predict a Role For Mir-103/mir-107 Paralogs Imentioning
confidence: 99%
“…MiR-103/7 are present in PANK genes, which serve to regulate metabolism (and this relationship holds constant through vertebrate evolution); 2. Prior studies suggest that intronic miRNAs are often expressed coordinately with their 'parent' protein-coding genes [15,16,18]; 3. MiR-103/7 levels are changed in states of altered cellular metabolism, including stress [48,65,66,68,69]; 4.…”
Section: Bioinformatics Predict a Role For Mir-103/mir-107 Paralogs Imentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas intergenic miRNAs are generally derived from independent precursors, intronic miRNAs may either be spliced out from the host gene pre-mRNA transcript or be processed from an independently transcribed precursor (Ying and Lin 2006). Comparison of the expression profiles of intronic miRNAs and their host genes (unpublished data) showed that, in general, less than 50 % of the intronic miRNAs were co-expressed (i.e., detected simultaneously) with their host genes.…”
Section: Intronic Mirna Loci May Be Independently Transcribedmentioning
confidence: 99%
“…Because of the flexibility of miRNA in binding with partially complementary mRNA targets, miRNA can serve as an anti-virus drug or vaccine to achieve a breakthrough in the treatment of virus mutation. Moreover, since miRNAs are single-stranded molecules insensitive to interferon systems, the utilization of this Pol-Ⅱ-mediated miRNA generation can be safe both in vitro and in vivo without the cytotoxic effects of dsRNAs and siRNAs [15] . These findings indicate that miRNA mediated RNAi can be used as a tool for gene-specific therapeutics against viral infections.…”
mentioning
confidence: 99%